Increased Circulating CD4+CXCR5+ Cells and IgG4 Levels in Patients with Myelodysplastic Syndrome with Autoimmune Diseases - Na Xiao; Xin He; Haiyue Niu; Hong Yu; Ningbo Cui; Hongzhao Li; Li Yan; Zonghong Shao; Limin Xing; Huaquan Wang (Journal of Immunology Research)
Objectives. Immune abnormalities play an important role in the pathogenesis and progression of myelodysplastic syndrome (MDS). Some patients with MDS have autoimmune diseases (AI). Follicular helper T (Tfh) cells help B cells produce antibodies. The role of Tfh in MDS with AI has not been studied. Methods. We enrolled 21 patients with MDS with AI and 21 patients with MDS without AI. The proportion of peripheral blood CD4+CXCR5+ cells and the PD1 expression on CD4+CXCR5+ cells were detected by flow cytometry. Serum levels of immunoglobulin G (IgG) and IgG4 were measured. The survival and progression of MDS to acute myeloid leukemia (AML) in MDS patients with or without AI were compared. Results. MDS with AI accounted for 19.6% of all MDS cases in our study. The overall response rate was 81% (17/21) in MDS patients with AI for the first-line treatment. The proportion of circulating CD4+CXCR5+ cells was increased, but the expression of PD1 was decreased in MDS patients with AI. Serum IgG4 levels were also increased in MDS patients with AI. The proportion of peripheral blood CD4+CXCR5+ cells and the level of serum IgG4 decreased after therapy, but the expression of PD1 increased. There were no differences in overall survival and progress to acute myeloid leukemia between MDS with AI and without AI groups. Conclusion. CD4+CXCR5+ cells and IgG4 levels increased in patients with MDS and AI.